ISO-DOSE MAP GENERATION AND DOSE-AREA PRODUCT CALCULATION THROUGH DIGITAL IMAGE PROCESSING OF SCANNED IRRADIATED RADIOCHROMIC FILMS. - RUIZ-GONZALEZ, Y.; RODRÍGUEZ-LEDESMA, S.; VIERA, J. E. PAZ; GINORI, J. V. LORENZO (Revista Cubana de Física)
Iso-dose maps creation and kerma-area products calculation are important procedures in radiotherapy and medical imaging. In this work, a method is presented to obtain iso-dose maps through digital processing of the images obtained from radiochromic films, which are employed to estimate the dose absorbed by the patient. The kerma-area product in selected regions of interest (ROIs) in the iso-dose map was then evaluated. The images were obtained by scanning the irradiated films using a commercial flatbed scanner. The iso-dose areas were extracted by means of an image segmentation algorithm, while calibration for a particular film to obtain a sensitometric curve relating dose to film darkening, was also made. A software interface allowed introducing the scanned image for the estimation of kerma-area products by defining the ROI interactively. The methods developed in this work allowed to implement a software application to obtain the iso-dose maps and kerma-area product in selected ROIs.